EVALUASI KINERJA BANGUNAN STRUKTUR BETON SISTEM RANGKA PEMIKUL MOMEN BERDASARKAN KRITERIA INDEKS KERUSAKAN - Rudi Kirana (Jurnal Teknik Sipil USU, 2014)
Abstract The design on the performance-based concept is commonly reposed upon the criterion of storey or interstorey drift in evaluating the structural performance under seismic excitation. Nonetheless, there are a few parameters affecting the structural performance besides drift, such as plastic deformation, dissipation energy, cyclic fatigue, and natural period of structure. In this paper, evaluation on the structural performance based on energy concept is interpreted in the value of Park and Ang damage index. The value of DI equaling to zero indicates no damage, DI ≥ 1 signifies the total collapse, and 0 ≤ DI ≤ 1 showing the degree of damage. The analytical method is done on 3 moment-resisting frame concrete structures under non-linier time history of Imperial Valley ground acceleration. The objective of this project is to investigate the degree of structural damage based on the criterion of damage index so that the structure can be repaired or demolished. The results of evaluation on damage index of three structures are model-1 structure with DI 0.443, model-2 structure with DI 0.878, model-3 structure with DI 0.325. This means that model-2 structure with irregular mass system giving the bad performance. Keywords: plastic deformation, cyclic fatigue, time history, Park and Ang damage index